2011
DOI: 10.2460/javma.238.12.1593
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of single-site and multiple-site disk fenestration on the rate of recurrence of thoracolumbar intervertebral disk herniation in dogs

Abstract: Multiple-site disk fenestration decreased the rate of recurrent IVDH in small-breed dogs, compared with the use of single-site disk fenestration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

6
83
2
3

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 20 publications
6
83
2
3
Order By: Relevance
“…However, strict criteria to define a breed as chondrodystrophic are lacking, 1,9,27 and it is currently unclear whether English Cocker Spaniels should be considered chondrodystrophic. [1][2][3][4]6,12,13,22,27,28 It has been demonstrated that English Cocker Spaniels have a less pronounced chondrodystrophic phenotype than Dachshunds. 5 The vertebral column length relative to the height at the withers (most dorsal aspect of the shoulders between the scapulae) was much higher in Dachshunds than in English Cocker Spaniels, but was similar between English Cocker Spaniels and German Shepherd Dogs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, strict criteria to define a breed as chondrodystrophic are lacking, 1,9,27 and it is currently unclear whether English Cocker Spaniels should be considered chondrodystrophic. [1][2][3][4]6,12,13,22,27,28 It has been demonstrated that English Cocker Spaniels have a less pronounced chondrodystrophic phenotype than Dachshunds. 5 The vertebral column length relative to the height at the withers (most dorsal aspect of the shoulders between the scapulae) was much higher in Dachshunds than in English Cocker Spaniels, but was similar between English Cocker Spaniels and German Shepherd Dogs.…”
Section: Discussionmentioning
confidence: 99%
“…3,4,[8][9][10][11][12] English Cocker Spaniels are also predisposed to IVDE, and this breed is among the 7 breeds at highest risk for this disorder. 2,5,6,13,14 Although anecdotal information suggests a higher incidence of lumbosacral IVDEs in English Cocker Spaniels than in other dog breeds, 15 little is known about characteristics of thoracolumbar and lumbar IVDE in this breed.…”
mentioning
confidence: 99%
“…Ultimately an ideal situation would be a randomized controlled study design in dogs undergoing spinal decompression with application of one of the prophylactic techniques along with a control group ultimately with comparison among groups. When considering the ease that PLDA may be performed in conjunction with other decompressive surgical procedures, level II evidence could be easily obtained as demonstrated by Brisson et al [17] in the case of fenestration. This accumulation of evidence with regard to PLDA may be obtained in an effi cient, easy and cost-effective manner allowing a signifi cant " boost " to the veterinary literature.…”
Section: Discussionmentioning
confidence: 99%
“…One study was a randomized controlled study (RCT) [17] . The remaining reports were Table 1 The fi ve steps of decision-making using an evidence-based medicine approach.…”
Section: Critical Analysis Of the Available Evidencementioning
confidence: 99%
See 1 more Smart Citation